The Effect of Organizational Commitment and Work Motivation on Employee Productivity of PT. RODATEKNINDO PURWAJAYA - Prayu Ivantri; Yun Fitriano; Yanto Efendi (Penerbit Jurnal Indonesia, 2023)
Rodateknindo Purajaya is a construction company in the implementation sector with the form of PT which has qualifications. This research aims to determine the effect of organizational commitment and work motivation on employees’ work productivity at PT. Rodateknindo Purajaya. This type of research is correlational, namely research to determine the influence and level of influence between two or more variables without any attempt to influence these variables. The sample in this study used a total sampling technique, where the entire population was sampled, amounting to 55 people. There is an influence of organizational commitment (X1) on work productivity (Y) at PT. Rodateknindo Purajaya Bengkulu is 0.000, so Ho is rejected and Ha is accepted. From the significance value obtained, variable X influences work productivity (Y). There is an influence of work motivation (X2) on work productivity (Y) at PT. Rodateknindo Purajaya Bengkulu is 0.031, so Ho is rejected and Ha is accepted. From the significance value obtained, the variable X2influences work productivity (Y).